Gifting translation in early modern England - Inglis, Kirsten (Amsterdam University Press, 2023)
Translation was a critical mode of discourse for early modern writers. Gifting Translation in Early Modern England: Women Writers and the Politics of Authorship examines the intersection of translation and the culture of gift-giving in early modern England, arguing that this intersection allowed women to subvert dominant modes of discourse through acts of linguistic and inter-semiotic translation and conventions of gifting. The book considers four early modern translators: Mary Bassett, Jane Lumley, Jane Seager, and Esther Inglis. These women negotiate the rhetorics of translation and gift-culture in order to articulate political and religious affiliations and beliefs in their carefully crafted manuscript gift-books. This book offers a critical lens through which to read early modern translations in relation to the materiality of early modern gift culture
9789463721202
Keywords: History; Art History; and Archaeology; Early Modern Studies; Literaturgeschichte und Literaturkritik; Vereinigtes Königreich; Großbritannien; Gender Studies; Geschlechtersoziologie; Gender and Sexuality Studies; Literary Theory; Criticism; and History; Early modern history: c 1450/1500 to c 1700; Gender studies: women; LITERARY CRITICISM / Renaissance; LITERARY CRITICISM / Subjects & Themes / Women *; Translation (history); Renaissance women writers; gift-giving (history); early modern political culture; material culture; manuscript circulation